2006
DOI: 10.1007/s00253-006-0419-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of polyunsaturated fatty acid producing Thraustochytrium species: screening of strains and optimization of omega-3 production

Abstract: An isolation program targeting Thraustochytrids (marine fungoid protists) from 19 different Atlantic Canadian locations was performed. Sixty-eight isolates were screened for biomass, total fatty acid (TFA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) content. Analysis of fatty acid methyl ester results discerned four distinctive clusters based on fatty acid profiles, with biomass ranging from 0.1 to 2.3 g L(-1), and lipid, EPA, and DHA contents ranging from 27.1 to 321.14, 2.97 to 21.25, and 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
110
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(128 citation statements)
references
References 21 publications
13
110
0
2
Order By: Relevance
“…The negative coefficient of glucose-yeast extract (BC) interaction compared to glucose-MSG (BD) most probably implies that MSG is the preferred nitrogen source compared to yeast extract. This finding is in agreement with that reported by Burja et al (2006) where supplying the culture of Traustochytrium sp. ONC-T18 with 10 g L −1 MSG replacing yeast extract resulted in 43% increment in DHA content of lipid.…”
Section: Ajassupporting
confidence: 83%
See 1 more Smart Citation
“…The negative coefficient of glucose-yeast extract (BC) interaction compared to glucose-MSG (BD) most probably implies that MSG is the preferred nitrogen source compared to yeast extract. This finding is in agreement with that reported by Burja et al (2006) where supplying the culture of Traustochytrium sp. ONC-T18 with 10 g L −1 MSG replacing yeast extract resulted in 43% increment in DHA content of lipid.…”
Section: Ajassupporting
confidence: 83%
“…Ren et al (2013) also suggested that MSG promotes DHA production. However, since high levels of both glucose and MSG are shown to have negative effect on biomass, it is desirable to use moderate levels of MSG in combination with high levels of glucose to increase DHA yield (Burja et al, 2006;Yokochi et al, 1998). This is important to overcome the inhibitory effect of glucose-MSG on the biomass production of this isolate.…”
Section: Ajasmentioning
confidence: 99%
“…The strains C36 and C22 for their high DHA concentrations, which were higher than what is described in the literature (Bajpai et al 1991, Burja et al 2006, Yamasaki et al 2006, Chi et al 2007. Rhodosporidium toruloides and Rhodotorula glutinis produce around 70 and 33.7% of total lipids in dry weight, respectively.…”
Section: Discussionmentioning
confidence: 39%
“…This study confirms the main advantages for using ISTE which include increased precision and accuracy, reduced time and labor costs, elimination of time-consuming pretreatment [27] and easy applicability for routine screening of new microbial isolates [4]. In this lab, replicable FAME data from small scale algal physiological experiments is routinely generated from biomass samples of *1 mg, something not easily achievable to the authors' knowledge with two-step extraction-transesterification procedures.…”
Section: Discussionmentioning
confidence: 51%
“…One of the challenges in resolving this question is the unclear meaning of various lipid content values reported in the scientific literature [19], generally referred to as 'oil content' or 'lipid content', with wideranging [25], and even unreferenced estimates commonly cited to make the case for microalgal biofuels [7]. In addition, there are researchers growing microbial heterotrophs [4] or algae heterotrophically [30], who consistently report higher lipid content values that may be included when modeling phototrophic biodiesel production as a sustainable fuel source. For example, the heterotrophic thraustochytrid Schizochytrium sp.…”
Section: Introductionmentioning
confidence: 99%